2016
DOI: 10.1007/978-3-319-22909-6_1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Biomarkers for Breast Cancer Risk

Abstract: Clinical risk assessment for cancer predisposition includes a three-generation pedigree and physical examination to identify inherited syndromes. Additionally genetic and genomic biomarkers may identify individuals with a constitutional basis for their disease that may not be evident clinically. Genomic biomarker testing may detect molecular variations in single genes, panels of genes, or entire genomes. The strength of evidence for the association of a genomic biomarker with disease risk may be weak or strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 136 publications
1
36
0
Order By: Relevance
“…Individuals who are heterozygous for a single pathogenic ATM variant have increased risk of adult onset breast, prostate and pancreatic cancer (1315). This also has implications for cancer screening in affected parents of children with A-T.…”
Section: Ataxia Telangiectasiamentioning
confidence: 99%
“…Individuals who are heterozygous for a single pathogenic ATM variant have increased risk of adult onset breast, prostate and pancreatic cancer (1315). This also has implications for cancer screening in affected parents of children with A-T.…”
Section: Ataxia Telangiectasiamentioning
confidence: 99%
“…Data from almost 400,000 women affected with breast cancer showed that 281 SNPs are significantly associated with the risk of this disease, which reduced to 233 risk loci when linkage disequilibrium was taken into account. These findings add new information to the already existing recent literature reviews on this subject, which report up to 172 common variants linked to breast cancer susceptibility (3,4,6,(67)(68)(69)(70)(71). These SNPs are estimated to account 15-20% of the genetic component of disease risk (3,72), which clearly implies that much more work is needed to fully elucidate the molecular basis of breast cancer predisposition.…”
Section: Discussionmentioning
confidence: 53%
“…Researchers have identified a number of risk factors for breast cancer, including penetrant gene mutations (Walsh et al, 2016) and genetic polymorphisms (Dunning et al, 1999), race (Chlebowski et al, 2005), age (Smigal et al, 2006), and breast density (McCormack and dos SS, 2006). Many of the identified risk factors are non-modifiable, however, and thus far, only a small percentage of breast cancer risk has been successfully linked to genetic inheritance (Oldenburg et al, 2007; Ghoussaini et al, 2013).…”
Section: Introductionmentioning
confidence: 99%